2012
DOI: 10.1093/infdis/jis670
|View full text |Cite
|
Sign up to set email alerts
|

First-in-Human Evaluation of the Safety and Immunogenicity of a Recombinant Adenovirus Serotype 26 HIV-1 Env Vaccine (IPCAVD 001)

Abstract: NCT00618605.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
137
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 29 publications
(45 reference statements)
12
137
0
3
Order By: Relevance
“…Table 1 shows the source and growth characteristics of these simian adenoviruses. The novel rhesus monkey adenovirus vectors were viable and grew to high titers, with ratios ranging from 3 to 30 vp/PFU, similar to those seen with human adenovirus vectors (data not shown), suggesting that these vectors might be suitable for large-scale production in the standard cell lines that are currently being utilized to manufacture human adenovirus vaccine vectors (1,35). We also constructed vectors that expressed various transgenes, including HIV/SIV Gag, Pol, Env, luciferase, and eGFP (data not shown), suggesting the generalizability of these vector platforms.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…Table 1 shows the source and growth characteristics of these simian adenoviruses. The novel rhesus monkey adenovirus vectors were viable and grew to high titers, with ratios ranging from 3 to 30 vp/PFU, similar to those seen with human adenovirus vectors (data not shown), suggesting that these vectors might be suitable for large-scale production in the standard cell lines that are currently being utilized to manufacture human adenovirus vaccine vectors (1,35). We also constructed vectors that expressed various transgenes, including HIV/SIV Gag, Pol, Env, luciferase, and eGFP (data not shown), suggesting the generalizability of these vector platforms.…”
Section: Resultsmentioning
confidence: 63%
“…A major research focus over the past several years has been the development of novel adenovirus vaccine vectors, apart from Ad5, that exhibit a lower seroprevalence in humans in the developing world. Most efforts to date have focused on alternative serotypes of human adenovirus vectors and chimpanzee adenovirus vectors, both of which are currently being evaluated in clinical trials (1,13,43,44). However, these vectors still show a degree of seroprevalence in the developing world, and human and chimpanzee adenoviruses exhibit interdigitating phylogeny.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…120,121 Ad26 and Ad35 studies have shown potential in phase I/II human vaccine trials. [122][123][124][125] A recent randomized, double-blind, placebo-controlled trial in 218 healthy adults using Ad26. EnvA.01 and Ad35.Env vectors in both homologous and heterologous combinations elicited humoral and cellular immune responses in nearly all participants.…”
Section: New Vectorsmentioning
confidence: 99%
“…There are approximately 60 different types of Ad divided into 7 species (A-G) (Wy Ip and Qasim, 2013). Researchers, including ourselves, have begun to look into the use of low-seroprevalent Ads as alternative viral vectored vaccines (Abbink et al, 2007;Waddington et al, 2008;Schuldt et al, 2012;Teigler et al, 2012;Zahn et al, 2012;Baden et al, 2013;Weaver, 2013;Weaver and Barry, 2013). While these alternative viral vectors may have a lower seroprevalence, the differences in their biology as compared with Ad5 have started to come into question.…”
Section: Introductionmentioning
confidence: 99%